Uji Aktivitas Antioksidan Ekstrak Daun Karet Kebo (Ficus Elastica) dengan Metode Peredaman Radikal Bebas Dpph (1,1-Diphenyl-2-Picrylhydrazil): Antioxidant Assay of Ficus Elastica Extract Leaf with Dpph Free Radical Scavenging (1,1-diphenyl-2-phycrilhydrazyl) - Handayani, Selpida; Kurniawati, Ida; Abdul Rasyid, Faradiba (Universitas Tadulako, 2020)
Ficus elastica leaf is one of the Ficus species assumed to be rich in polyphenols so that it can act as an antioxidant. The research aimed to determine the antioxidant activity and IC50 value of methanol and water extracts of rubber leaf. In this research, the extraction was conducted by maceration using methanol and obtained the yield value of 7,03%, while the infundation using water obtained the yield value of 2,82%. The antioxidant activity test was conducted by DPPH free radical scavenging (1,1-diphenyl-2-phycrilhydrazyl) using a quercetin comparator. The qualitative tests were conducted by TLC method using dicloromethane:methanol eluent with a ratio of 99:1 for methanol extracts, and a ratio of 95:5 for water extracts, where all extracts of both methanol and water positively container antioxidants characterized by the formation of yellow spots with a purple background on TLC plates. The results of the quantitative test shower that the methanol extract had medium antioxidant activity with an IC50 value of 78,39 µg/mL, and water extract had an inactive antioxidant activity with an IC50 value of 319,11 µg/mL. While quercetin was classified as a very strong antioxidant with an IC50 value of 7,62 µg/mL.